Christopher Columbus : A Demystification (مجلة الواحات للبحوث والدراسات, 2014)
was in Lagos and soon after gaining strength he made his way to Lisbon, where he found a large community of Genoese merchants and shipbuilders.  At that time he was 25 and Lisbon was a haven for sailors, merchants, adventurers, entrepreneurs and others whose lives depended on seagoing. His brother Bartholomew was a mapmaker there and sometimes they worked together. In 1478 or 1479 he married Felipa Perestrello e Moniz from a noble family, which would later help him with the court in access to the documents related to sea navigation such as maps, currents, interviews with sailors, etc. The newlyweds went to live in Porto Santo, a city in the Portuguese island of Madeira which was now governed by Felipa’s elder brother after the death of her father. It was 1480 or 1481 and there Diego, his first son, was born and Felipa died shortly thereafter.